Longing for Symbolic Capital in Toni Morrison’s The Bluest Eye: A Bourdieun Estimation - Hossain, MD Mozaffor (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2022)
Toni Morrison’s The Bluest Eye portrays, among other both white and black lives in a less significant mark, the life of a young black girl named Pecola Breedlove whose desperate longing for owning the bluest eyes so as to free herself from the shame and disgrace of her birthed identity has inspired the author to name the novel so. Morrison inserted into the protagonist her (Morrison’s) depraved experience of injustice, inequality, racial discrimination, social stigmatization and, above all, inborn physical outlook, wielded upon the black communities in America during her (Morrison’s) time. While brooding over the question why a black girl would hanker after the bluest eyes, I find the hints, specified descriptions and clarified answers provided by Morrison in the novel logically matched with “Symbolic Capital”, the last of the four capitals delineated by the French philosopher and public intellectual Pierre Bourdieu (1930-2002). Accordingly, this article seeks to appraise Pecola’s yearning for the bluest eyes in Toni Morrison’s The Bluest Eye through Bourdieu’s theory of “Symbolic Capital”.